Mediation in Special Education. Technical Assistance Paper - Florida State Dept. of Education, Tallahassee. Bureau of Education for Exceptional Students; Florida State Dept. of Education, Tallahassee. Bureau of Education for Exceptional Students ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
Mediation in special education is a process intended to assist parents, schools, and agencies in resolving disagreements regarding the special education program of a student with disabilities. A trained mediator works with the parties to guide them toward a mutually satisfactory solution that meets the best interests of the student. This occurs at a nonadversarial session which is more structured than a parent-school conference, but less formal than a due process hearing. This technical assistance paper contains an overview of special education mediation in Florida, an explanation of the process, a description of each party's role in the process, a comparison of mediation and due process hearings, answers to commonly asked questions about mediation, and copies of forms used in the process. The appendix contains the following forms: a request for mediation, mediation agreement, mediator evaluation of the mediation session, and participant evaluation of the mediation session. (JDD)
Administrators.
Practitioners.
Parents.
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Disabilities; Due Process; Elementary Secondary Education; Grievance Procedures; Negotiation Agreements; Parent School Relationship; Problem Solving; Special Education; State Programs; Student Placement; Florida -- Mediation; Guides, Non-Classroom.